A User-Friendly Procedure for the Preparation of Secondary Alkyl Chlorides - Cahiez, Gérard; Lefèvre, Nicolas; Poizat, Maël; Moyeux, Alban (Synthesis, 2013)
Secondary alkyl chlorides have been efficiently prepared from secondary alkyl sulfonates under mild and user-friendly conditions. The exchange reaction was generally performed by using benzyltributylammonium chloride in acetone (reflux, 30 min). Yields are excellent from functionalized, base-sensitive and hindered secondary alkyl sulfonates.
Keywords: nucleophilic substitution; sulfonates; secondary alkyl chlorides; quaternary ammonium halides; sulfonate–halogen exchange